1955
DOI: 10.1021/jo01364a025
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR REARRANGEMENTS. VI.1 THE REARRANGEMENT OF OXIMES ON REDUCTION WITH LITHIUM ALUMINUM HYDRIDE

Abstract: Reductions with lithium aluminum hydride have been characterized by the high degree of predictability of the products (1). In a few instances groups were anomalously reduced due to the structure of the compound treated with this reagent (1). Recently, however, three interesting molecular rearrangements have been reported to occur with lithium aluminum hydride indicating a new type of reaction with this reagent. Cram (2) has shown that the phenyl groups of the ptoluenesulfonic acid esters of either 2-phenyl-3-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1963
1963
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 3 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…The ketones chosen for the study were selected with the aim of determining how facile and versatile a mechanochemical process is for ketone-oxime transformations, and for identifying possible limitations of the process. Five ketones were decorated with an electron withdrawing substituent (1-5), two of them had an electron donating substituent (6 and 7), eight ketones contained structurally active functional groups such as -OH (8 and 9), -NH 2 (10 and 11) and a pyridyl group (12)(13)(14)(15), two were multifunctionalized (16 and 17) and finally, three aliphatic ketones (18)(19)(20) were used (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ketones chosen for the study were selected with the aim of determining how facile and versatile a mechanochemical process is for ketone-oxime transformations, and for identifying possible limitations of the process. Five ketones were decorated with an electron withdrawing substituent (1-5), two of them had an electron donating substituent (6 and 7), eight ketones contained structurally active functional groups such as -OH (8 and 9), -NH 2 (10 and 11) and a pyridyl group (12)(13)(14)(15), two were multifunctionalized (16 and 17) and finally, three aliphatic ketones (18)(19)(20) were used (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A facile, solvent-assisted and room-temperature mechanochemical synthetic pathway for the generation of ketoximes from ketones has been explored. The robustness and versatility of this simple process has been illustrated by performing the reaction on 20 different ketones with electron withdrawing (1-5), electron donating (6 and 7), structurally active groups (8)(9)(10)(11)(12)(13)(14)(15), multifunctionalized (16 and 17) and aliphatic compounds (18)(19)(20). Several competitive experiments have shown that electronic factors (as induced by substituents on the aromatic backbone) can influence the relative reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Lithium aluminum hydride is often used for this transformation, but it is sometimes difficult to separate from the concomitant rearranged products in the case of phenylketone oximes. 14 9) or MoO 3 . 9) Among the above additives, Ipaktschi's procedure using MoO 3 gave the best results for the present oximes.…”
Section: Resultsmentioning
confidence: 99%